STRATEGIES FOR AMPLIFYING INDUSTRY'S ROLE IN UZBEKISTAN'S ECONOMIC GROWTH - Jumaev, Nodir H.; Zayniev, Farkhod N. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article analyzes the practical situations of the industrial sector in Uzbekistan. Practical suggestions and recommendations are presented regarding the development of the industry in strengthening the economy of Uzbekistan